(untitled) (Andamios, Revista de Investigación Social, 2008)
Our article shows how the notion of practices constitutes the point of departure of the cognitive proposition found in the works of Giambattista Vico (1668-1744) and Karl Marx (1818-1883). Praxis, conceived as the specific form in which human beings seek to satisfy our spiritual and material necessities, is transformed, given this specificity in the Demiurge of history, and blazes its own trail. Thus considered, praxis is an essentially immanent phenomenon. Our findings show, however, that praxis also struggles to recover infinity, to transcend. Through the search for satisfaction of this necessity praxis becomes the bearer of the fight for transcendence and, beyond that, the vehicle par excellence of its search.